A data transmission method for particle physics experiments based on Ethernet physical layer*Supported by National Natural Science Foundation of China (11005107) and Independent Projects of State Key Laboratory of Particle Detection and Electronics (201301). (November 2015) - Huang 黄, Xi-Ru 锡汝; Cao 曹, Ping 平; Zheng 郑, Jia-Jun 佳俊
Abstract: Due to its advantages of universality, flexibility and high performance, fast Ethernet is widely used in readout system design for modern particle physics experiments. However, Ethernet is usually used together with the TCP/IP protocol stack, which makes it difficult to implement readout systems because designers have to use the operating system to process this protocol. Furthermore, TCP/IP degrades the transmission efficiency and real-time performance. To maximize the performance of Ethernet in physics experiment applications, a data readout method based on the physical layer (PHY) is proposed. In this method, TCP/IP is replaced with a customized and simple protocol, which makes it easier to implement. On each readout module, data from the front-end electronics is first fed into an FPGA for protocol processing and then sent out to a PHY chip controlled by this FPGA for transmission. This kind of data path is fully implemented by hardware. From the side of the data acquisition system (DAQ), however, the absence of a standard protocol causes problems for the network related applications. To solve this problem, in the operating system kernel space, data received by the network interface card is redirected from the traditional flow to a specified memory space by a customized program. This memory space can easily be accessed by applications in user space. For the purpose of verification, a prototype system has been designed and implemented. Preliminary test results show that this method can meet the requirements of data transmission from the readout module to the DAQ with an efficient and simple manner.